2021
DOI: 10.1016/j.xjidi.2021.100021
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine RNA In Situ Hybridization Permits Individualized Molecular Phenotyping in Biopsies of Psoriasis and Atopic Dermatitis

Abstract: Detection of individual cytokines in routine biopsies from patients with inflammatory skin diseases has the potential to personalize diagnosis and treatment selection, but this approach has been limited by technical feasibility. We evaluate whether a chromogen-based RNA in situ hybridization approach can be used to detect druggable cytokines in psoriasis and atopic dermatitis. A series of psoriasis (n ¼ 20) and atopic dermatitis (n ¼ 26) biopsies were stained using RNA in situ hybridization for IL4, IL12B (IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 34 publications
4
33
0
Order By: Relevance
“…As BAL might not fully reflect granulomas in the lung parenchyma, we also studied immunologic patterns in tissue containing parenchymal pulmonary granulomas from sarcoidosis patients ( n = 10) and compared them to cutaneous sarcoidosis ( n = 10) and controls ( Supplementary Table 6 ) . We utilized RNA in situ hybridization to stain for key cytokine markers of immune polarization including Th1 ( IFNG ), Th2 ( IL13 ), and Th17 ( IL17A ) 35 . We also included cutaneous inflammatory disorders with canonical Th2 (atopic dermatitis) and Th17 (psoriasis) polarization as positive controls to contextualize patterns seen in sarcoidosis 35 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As BAL might not fully reflect granulomas in the lung parenchyma, we also studied immunologic patterns in tissue containing parenchymal pulmonary granulomas from sarcoidosis patients ( n = 10) and compared them to cutaneous sarcoidosis ( n = 10) and controls ( Supplementary Table 6 ) . We utilized RNA in situ hybridization to stain for key cytokine markers of immune polarization including Th1 ( IFNG ), Th2 ( IL13 ), and Th17 ( IL17A ) 35 . We also included cutaneous inflammatory disorders with canonical Th2 (atopic dermatitis) and Th17 (psoriasis) polarization as positive controls to contextualize patterns seen in sarcoidosis 35 .…”
Section: Resultsmentioning
confidence: 99%
“…We utilized RNA in situ hybridization to stain for key cytokine markers of immune polarization including Th1 ( IFNG ), Th2 ( IL13 ), and Th17 ( IL17A ) 35 . We also included cutaneous inflammatory disorders with canonical Th2 (atopic dermatitis) and Th17 (psoriasis) polarization as positive controls to contextualize patterns seen in sarcoidosis 35 . We found significant expression of IFNG in lymphocytes in the sarcoidosis cases, but not normal lung or skin (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, by measuring the expression of interleukin 4, interleukin 13 versus interleukin 23, and interleukin 17A and F transcripts, we have found that we can distinguish AD from psoriasis. 2 We have also recently used this approach to evaluate a patient who was treated with dupilumab for moderate-to-severe AD and who had an excellent response to but in whom psoriasiform dermatitis subsequently developed 8 months after dupilumab initiation. Cytokine RISH was performed on a biopsy specimen taken before the patient started dupilumab as well as on a specimen of the subsequent psoriasiform dermatitis.…”
mentioning
confidence: 99%